KINERJA KEUANGAN, CORPORATE SOCIAL RESPONSIBILITY, DAN PERAN EARNINGS PER SHARE - Ahmad Iskandar Rahmansyah; Umi Rahma Dhany (Universitas Riau Kepulauan, 2023)
In the contemporary business era, Corporate Social Responsibility (CSR) has evolved into a profound and far-reaching phenomenon. Businesses are no longer solely evaluated from a profitability perspective, but also in terms of their consideration of the social and environmental impacts of their operations. This phenomenon has raised crucial questions about how a company's financial performance affects its commitment to CSR. This research aims to investigate the relationship between a company's financial performance, measured through Return on Assets (ROA), Current Ratio (CR), Turnover Receivable (TR), and Debt-to-Equity Ratio (DER), and its commitment to CSR. Furthermore, it introduces Earnings Per Share (EPS) as a moderator and mediator in the influence of each financial performance metric on CSR. This study employs a quantitative research approach, gathering data from company annual reports obtained from the official IDX website. Data analysis is conducted using the SmartPLS 3 application. The results of the analysis reveal that ROA has a significant positive impact on CSR, with EPS acting as a mediator, while CR, TR, and DER do not significantly influence CSR.